Urban Regeneration and Sustainable Building Transformation: Wood As a Building Material - Alberto CERVESATO (International Journal of Environmental, Sustainability, and Social Science, 2023)
The current cultural debate in urban and architectural fields - but not only - sees the emergence of increasing attention to environmental sustainability and related issues, which inevitably condition all the different phases of the project. Reducing land consumption, coping with climate change, improving the energy efficiency of buildings, as well as increasing their level of living comfort, are just some of the goals to be pursued to achieve a generalized improvement of the built environment through application of the typical principles of the so-called urban regeneration. Looking at the internal areas of the Italian territory, concepts are evoked such as the reuse of materials, the reconversion of buildings and sometimes the renaturalization, which is a less usual choice for a highly man-made territory like the Italian one. In this case, therefore, the use of wood as a preferential material for the aforementioned operations, a material which, over the last few decades, has greatly improved from a structural and performance point of view. Finally, a proposal will be made, carried out with the Municipality of Resia, moved precisely by these principles and aimed at being a sort of â€œmodelâ€ - and also a stimulus - for the future of planning in these areas.